PENGARUH KERAPATAN WIREMESH TERHADAP KAPASITAS LENTUR PELAT BETON RINGAN KOMPOSIT - Jonathan Aaron; Widodo Kushartomo (JMTS: Jurnal Mitra Teknik Sipil, 2023)
Lightweight concrete is a concrete technology innovation that is currently being developed.. The advantage of lightweight concrete is that it uses less time and costs less compared to conventional concrete but has a weakness, that is lower strength. In this study, tests were carried out on the flexural capacity of composite lightweight concrete slabs to determine if lightweight concrete could be used as a structure or vice versa. The test is carried out by distributing the load evenly and gradually until the plate collapses. From the test results, a lightweight concrete slab without wiremesh reinforcement collapsed at a load of 560 kg, a lightweight concrete slab with 10x10 cm wiremesh reinforcement collapsed at a load of 800 kg, and a lightweight concrete slab with 15x15 cm wiremesh reinforcement collapsed at a load of 680 kg. From these results, we obtained the flexural strength of lightweight concrete slabs without wiremesh reinforcement of 1.86 MPa, lightweight concrete slabs with 10×10 cm wiremesh reinforcement of 2.567 MPa, and lightweight concrete slabs with 15×15 cm wiremesh reinforcement of 2.214 MPa. These three lightweight concrete slabs can be used as structures, but with a design load that is not too high. Abstrak Beton ringan merupakan inovasi teknologi beton yang sedang berkembang saat ini. Kelebihan beton ringan yaitu menggunakan waktu dan biaya yang lebih sedikit dibandingkan dengan beton pada umumnya tetapi mempunyai kelemahan yaitu kekuatan yang lebih rendah. Pada penelitian ini, pengujian dilakukan terhadap kapasitas lentur pelat beton ringan komposit untuk mengetahui jika beton ringan dapat digunakan sebagai struktur atau sebaliknya. Pengujian dilakukan dengan cara memberikan beban merata secara bertahap sampai pelat mengalami keruntuhan. Dari hasil pengujian, pelat beton ringan tanpa perkuatan wiremesh runtuh pada beban 560 kg, pelat beton ringan dengan perkuatan wiremesh 10×10 cm runtuh pada beban 800 kg, dan pelat beton ringan dengan perkuatan wiremesh 15×15 cm runtuh pada beban 680 kg. Dari hasil tersebut, didapat kuat lentur pelat beton ringan tanpa perkuatan wiremesh sebesar 1,86 MPa, pelat beton ringan dengan perkuatan wiremesh 10×10 cm sebesar 2,567 MPa, dan pelat beton ringan dengan perkuatan wiremesh 15×15 cm sebesar 2,214 MPa. Ketiga pelat beton ringan tersebut dapat dipakai sebagai struktur, tetapi dengan perencanaan beban yang tidak terlalu tinggi.